Comparative Study of Alfamart Employee Salary Deductions Due to Goods Difference Notes (NSB) (Analysis of MUI Fatwa No. 112/DSN-MUI/X/2017 and Law No. 13 Year 2003) - Mahesa, Arya; Zuhri, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2024)
There is a difference of opinion between the MUI Fatwa and the Labor Law regarding the permissibility of deducting employee salaries as a result of Nota Selisih barang (NSB). Because of this difference, an in-depth study or research is needed on the practice of deducting employee salaries, which in this case is focused on one of the largest retail companies in Indonesia, namely Alfamart as one of the subsidiaries of the company managed by PT Sumber Alfaria Tbk. This research aims to find out the practice of deducting employee salaries, and the similarities and differences of opinion between them. The type of research that the author uses is normative-empirical legal research with a qualitative approach. From the research conducted by the author, the perspective of the MUI Fatwa says that workers are not obliged to bear the risk of losses arising from their actions, because this violates the elements of mukhalafat Syuruth and violates the valid conditions in the contract. So in the author's opinion, the opinion of Fatwa MUI's Fatwa opinion is more relevant in relation to the case. Meanwhile, according to the Labor Law, sanctions may be imposed in the form of fines or deductions from wages and the employment contract between Alfamart and the employee is in accordance with the Labor Law.Keywords: Salary Deduction; Alfamart; Fatwa MUI; Employment Laws